Advances in Heavy Metal Bioremediation: An Overview - Ali Sayqal; Omar B. Ahmed (Applied Bionics and Biomechanics)
The pollution of toxic heavy metals is considered one of the most important environmental issues which has accelerated dramatically due to changing industrial activities. This review focuses on the most common methods, strategies, and biological approaches of heavy metal bioremediation. Also, it provides a general overview of the role of microorganisms in the bioremediation of heavy metals in polluted environments. Advanced methods of heavy metal remediation include physicochemical and biological methods; the latter can be further classified into in situ and ex situ bioremediation. The in situ process includes bioventing, biosparging, biostimulation, bioaugmentation, and phytoremediation. Ex situ bioremediation includes land farming, composting, biopiles, and bioreactors. Bioremediation uses naturally occurring microorganisms such as Pseudomonas, Sphingomonas, Rhodococcus, Alcaligenes, and Mycobacterium. Generally, bioremediation is of very less effort, less labor intensive, cheap, ecofriendly, sustainable, and relatively easy to implement. Most of the disadvantages of bioremediation relate to the slowness and time-consumption; furthermore, the products of biodegradation sometimes become more toxic than the original compound. The performance evaluation of bioremediation might be difficult as it has no acceptable endpoint. There is a need for further studies to develop bioremediation technologies in order to find more biological solutions for bioremediation of heavy metal contamination from different environmental systems.